Global Surgery - A review of the paediatric surgical workforce in South Africa - Dell, Angela June (Department of Surgery, 2019)
There is limited data with regard to the available paediatric surgical workforce in South Africa as well as their employment prospects upon completion of their specialisation training. These data are essential in developing a National Surgical Plan to address the burden of surgical disease as well as determining where resource allocation is needed. In addition, specialist paediatric surgeons who are unable to find suitable employment are more likely to emigrate, leading to further collapse of the surgical health care system. This aim of this study was to quantify and analyse the paediatric surgical workforce in South Africa as well as to determine their geographic and sector distribution. This research builds on previous research conducted in the field of general surgery and continues to grow the national database on surgical resource in South Africa. This study involved a quantitative descriptive analysis of all registered specialist as well as training paediatric surgeons in South Africa, and included their demographic data, the geographic location of their practice, as well as the sector in which they work. Quantitative data included their plans for public, private or dual practice once they have completed their specialization training. The results showed 2.6 paediatric surgeons per one million population under 14 years. More than half (69%) were male and the median age was 46.8 years. There were however, more female surgical registrars currently in training. The majority of the paediatric surgical practitioners were found in Gauteng (43%), followed by the Western Cape (26%) and Kwa-Zulu Natal (16%). The majority of specialists reportedly worked in the public sector (40.9%), however this number may have been over-reported as hours spent in public practice were not specified. Interprovincial differences as well as intersectoral differences were marked indicating geographic and socioeconomic maldistribution of paediatric surgeons. The public sector paediatric surgeon density (per million population under 14 years) was 2.4 which fell below the private sector paediatric surgeon density of 9.4. These numbers fell far below developed countries such as the United States, Germany and the Netherlands but the private sector density compared favourably with Ireland and Canada. Access to paediatric surgical care requires an adequate supply of experienced surgeons distributed over a wide geographical area. Additionally, paediatric surgeons require a wide range of ancillary support staff and hospital facilities. Without these resources, surgical access for the most vulnerable of populations is limited. Addressing the maldistribution of paediatric surgical workforce requires concerted efforts to expand existing training posts as well as equipping the remainder of level three hospitals to provide paediatric surgical training.